S-shaped Wound Closure Technique for Dumbbell-shaped Keloids - Komatsu, Seiji (Plast Reconstr Surg Glob Open, 2017)
Dog-ear collection, Z-plasty, and W-plasty are often performed for excision of dumbbell-shaped keloids; however, these procedures require additional incisions or excision of normal skin. Thus, an S-shaped wound closure technique was performed. The keloid lesions were extralesionally excised above the deep fascia, and the wound edges were shifted in opposite directions along the major axis to form an S-shape. The incision was closed by applying deep fascial sutures, subcutaneous sutures, and superficial sutures. Postoperative external beam radiation therapy was started within 6 hours after surgery at a dose of 20 Gy applied in 4 fractions. All wounds were covered with silicone-gel sheeting and fixed with tape after suture removal. No intralesional corticosteroid injection or oral tranilast was administered. Corticosteroid tape was applied in cases with suspected postoperative recurrence. Scoring was performed using the Manchester Scar Scale. A total of 8 lesions were treated. Temporary erythema and scar elevation were observed in 2 chest lesions; however, both were flattened and turned white using corticosteroid tape. Other than these 2 lesions, there was no recurrence or complication. The mean score improved from 15.8 to 7.2. The S-shaped wound closure technique has 3 advantages. First, no additional incision or excision is required, and additional scarring and keloid recurrence can be avoided. Second, aesthetic results are good, and noticeably long and zigzag-shaped scars can be avoided. Third, dispersion of tension on the scar can be expected. Although the S-shaped wound closure technique has limited application, it is a useful option for keloid treatment.